Refining instantaneous frequency estimation: Tackling abrupt transitions in aliased non-stationary signals - Sadiq Ali; Nabeel Ali Khan (Franklin Open)
Many real-life non-stationary signals, such as jammers or communication signals, exhibit abrupt transitions in instantaneous frequency. Estimating instantaneous frequencies of such signals is vital in applications involving interference mitigation in Global Navigation Satellite System and jammer localization. In this paper, a method is developed to estimate the Instantaneous Frequency curve in such challenging scenarios, where multi-component signals have abrupt transitions and intersect each other in the time–frequency domain. The proposed Instantaneous Frequency estimation algorithm is further extended by adding a refinement mechanism where the crude estimates of Instantaneous Frequencies are further improved through the re-estimation stage. The Instantaneous Frequency of each component is estimated individually by removing all the remaining components. Experimental results are presented, indicating that the proposed method outperforms the existing methods.